(untitled) (Research, Society and Development, 2020)
This is a qualitative research that aimed to develop and present an overview of publications about the use of games for teaching mathematics in four journals. The selected journals were: Boletim de Educação Matemática (Bolema), Zetetiké, Revista de Educação Matemática (REMat) and Educação Matemática em Revista (EMR). Searches were made on the online pages of journals for articles that had the word games and/or expressions as games for teaching mathematics in their title, abstract or keywords. In the analyzes, carried out through the full reading of the 18 selected texts, four general themes were identified: Proposal for teaching through games, application of games in the teaching of mathematics, theorizing about the use of games for the teaching of mathematics and games as an argumentative resource to deal with mathematics. A finding of this research was the fact that most publications involve elementary education. It is inferred that this must happen for the reason of the game bringing the mathematical content closer to a less formal context and providing the institutionalization of the contents gradually from the situations of games. An important observation concerns the small number of publications (18) about the use of games for teaching mathematics found in these journals, considering that the total period was 26 years of publications of the analyzed journals. This may indicate that there is a gap in research that deals with the use of games for teaching and learning mathematics.